2011
DOI: 10.1186/1749-8090-6-37
|View full text |Cite
|
Sign up to set email alerts
|

Is there an optimal minimally invasive technique for left anterior descending coronary artery bypass?

Abstract: BackgroundThe aim of this retrospective study was to evaluate the clinical outcome of three different minimally invasive surgical techniques for left anterior descending (LAD) coronary artery bypass grafting (CABG): Port-Access surgery (PA-CABG), minimally invasive direct CABG (MIDCAB) and off-pump totally endoscopic CABG (TECAB).MethodsOver a decade, 160 eligible patients for elective LAD bypass were referred to one of the three techniques: 48 PA-CABG, 53 MIDCAB and 59 TECAB. In MIDCAB group, Euroscore was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 13 publications
(16 reference statements)
1
45
1
Order By: Relevance
“…The conversion and severe postoperative complication rate was lower in this study than reported elsewhere [8,9,18,20,21]. No death or conversion to median sternotomy occurred in either both the TECAB or MINICAB groups, and postoperative bleeding occurred in 1% of the TECAB group during the learning curve.…”
Section: Commentcontrasting
confidence: 79%
See 1 more Smart Citation
“…The conversion and severe postoperative complication rate was lower in this study than reported elsewhere [8,9,18,20,21]. No death or conversion to median sternotomy occurred in either both the TECAB or MINICAB groups, and postoperative bleeding occurred in 1% of the TECAB group during the learning curve.…”
Section: Commentcontrasting
confidence: 79%
“…Although the early clinical results of robotic CABG were excellent with acceptable graft patency [19], the longer term graft patency and the freedom from mortality and morbidity were still unclear. For TECAB, Bonatti and colleagues [20] analyzed the 5-year results and reported survival rates of 95.8% and 93.9% for single-and double-vessel disease, respectively [20], while Jegaden and colleagues [21] reported a 96% survival and 88% freedom form re-intervention at 3 years after surgery, and a study [22] showed a graft patency of 92.7% at 8 years after TECAB. Fewer studies on MINICAB were reported.…”
Section: Commentmentioning
confidence: 96%
“…After exclusion of duplicated studies and 546 irrelevant articles based on abstracts and titles, 126 studies remained for full-text evaluation. Of these, 44 studies met the inclusion criteria, including nine studies in the TECAB off-pump group (10)(11)(12)(13)(14)(15)(16)(17)(18); two studies in the TECAB on-pump group (19,20); and 16 studies in the robotic MIDCAB group (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study, however, described this endpoint at 5-years and included complex hybrid interventions in patients with multi-vessel disease (7). Freedom from angina rates in the studies that reported on earlier time points ranged from 85% to 100% (1,2,6,11). Out of the larger CABG studies, the ARTS trial demonstrated a 5-year angina recurrence rate of 15.5% for CABG, and 21.2% for percutaneous coronary intervention (PCI) using bare metal stents (14).…”
Section: Freedom From Anginamentioning
confidence: 99%